Implementation of Android-Based Vehicle Tracking System in Trac Astra Rent A Car Palembang - Irman Effendy; Fatoni Fatoni (Journal of Information System and Informatics, 2020)
TRAC Astra Rent A Car is a leading car rental service provider in Indonesia, which also has a branch in the city of Palembang. Starting with only 5 units of vehicles, now PT. TRAC Astra Rent A Car rental car into a business unit that has more than 12,000 vehicles operating in more than 1,500 corporate customers segment. PT.TRAC help corporate customers improve efficiency in the transportation business and enable them to concentrate on their core business. Besides short-term car rental needs a safe and comfortable can be easily fulfilled because PT.TRAC location very easy to reach. With the development of information technology today, it would need to complete the management PT.TRAC which she rented vehicle with a tracking facility (tracking) the vehicle's location in real-time so that management can monitor the location where the vehicle which she rented was with the development of Android-Based Tracking system